Literature Review tentang Hubungan Psikologis terhadap Kejadian Hiperemesis Gravidarum: Literature Review about the Relationship Between Psychology on the Hyperemesis Gravidarum Occurrence - Vaya Luthfi Salsabila Anshory; Nurul Hasanah; Novia Fransiska Ngo (Jurnal Sains dan Kesehatan, 2022)
Nausea and vomiting affect up to >50% of pregnancies. Hyperemesis gravidarum is vomiting that occurs in early pregnancy until 20 weeks of gestation. The incidence of hyperemesis gravidarum in Indonesia is still quite a lot. The cause of this disease cannot be known with certainty, but it is carefully adjusted by thyroid hormone, Helicobacter pylori infection, and psychology. This study use literature review as a research method. This literature review study aims to determine the relationship between psychology on the hyperemesis gravidarum occurrence. Searches were performed by searching articles using electronic databases or search engines i.e Google Scholar, Harzing’s Publish, and Pubmed. The year of publication was limited between 2016 and 2021 in Indonesian and English language. The results were obtained 27 studies from International and Regional journals that are suitable with the inclusion criteria. The number of samples was 654.363 pregnant women are devided into case and control groups. The results of this literature review showed that psychology was found to be associated with hyperemesis gravidarum (96,3%). It can be concluded that psychological factors were found to be associated with the hyperemesis gravidarum occurrence.